Charging effect on current conduction in aluminum nitride thin films containing Al nanocrystals - Liu, Yang (2010)
The presence of Al nanocrystals (nc-Al) in AlN thin films is found to enhance the current conduction of the thin film system greatly due to the formation of tunneling paths of nc-Al arrays, and the nc-Al/AlN system shows a quasi-two-dimensional transport following a power law. However, charge trapping in nc-Al reduces the current conduction because of the increase in the tunneling resistance and/or the breaking of some tunneling paths due to Coulomb blockade effect. The current conduction also evolves with a trend towards one-dimensional transport due to the breaking of some transverse tunneling paths as a result of the charge trapping.